PENGARUH MEDIA SOSIAL TERHADAP KEHARMONISAN PASANGAN SUAMI ISTRI : Desa Ganjaran Kec Gondanglegi - Hasbulloh Huda, Muhammad; Rahmat Arwata, Danang (MAQASHID, 2024)
The growing sophistication of social media has brought both positive and negative impacts on social interactions, including within family relationships. This study adopted a descriptive qualitative method, incorporating observations and in-depth interviews with several married couples. The findings indicate that unwise use of social media can result in conflicts such as jealousy, infidelity, and marital breakdown. On the other hand, social media also plays a constructive role by facilitating long-distance communication and enabling families to share significant moments. This research highlights the importance of responsible social media usage to maintain family harmony, especially in the face of modernization and technological advancements.